2016
DOI: 10.1042/bcj20160390
|View full text |Cite
|
Sign up to set email alerts
|

The pro-inflammatory cytokines IFNγ/TNFα increase chromogranin A-positive neuroendocrine cells in the colonic epithelium

Abstract: The gastrointestinal tract is the largest hormone-producing organ in the body due to a specialized cell population called enteroendocrine cells (EECs). The number of EECs increases in the mucosa of inflammatory bowel disease patients; however, the mechanisms responsible for these changes remain unknown. Here, we show that the pro-inflammatory cytokines interferon γ (IFNγ) and tumor necrosis factor α (TNFα) or dextran sulfate sodium (DSS)-induced colitis increase the number of EECs producing chromogranin A (CgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…227,228 Recent studies have shown that the pro-inflammatory cytokines interferon (IFN)g and TNFa increase CgA þ eecs in an autophagy and protein kinase B (Akt) dependent manner. 229 Bromodeoxyuridine (BrdU) pulse-chase labeling of proliferative cells has demonstrated that increases in 5-HT þ cells during TNBS-colitis are due to alterations in the stem-cell niche rather than division of existing eecs. 230 Collectively this points to cytokine mediated alterations of specific eec subsets via adaptation at the stem-cell niche as opposed to proliferation of existing eecs.…”
Section: Mechanistic Cross-talk Between Enteroendocrine Cells and Immmentioning
confidence: 99%
“…227,228 Recent studies have shown that the pro-inflammatory cytokines interferon (IFN)g and TNFa increase CgA þ eecs in an autophagy and protein kinase B (Akt) dependent manner. 229 Bromodeoxyuridine (BrdU) pulse-chase labeling of proliferative cells has demonstrated that increases in 5-HT þ cells during TNBS-colitis are due to alterations in the stem-cell niche rather than division of existing eecs. 230 Collectively this points to cytokine mediated alterations of specific eec subsets via adaptation at the stem-cell niche as opposed to proliferation of existing eecs.…”
Section: Mechanistic Cross-talk Between Enteroendocrine Cells and Immmentioning
confidence: 99%
“…The CgA cell density is increased in patients with IBD, and in animal models of human UC and CD, with the exception of trinitrobenzene sulfonic acid (TNBS)-induced colitis[ 9 , 117 , 244 - 248 ] (Figure 3 ). The administration of the proinflammatory cytokines INFγ and TNFα and the induction of colitis by dextran sodium sulfate (DSS) in mice were found to increase the number of CgA cells[ 249 ].…”
Section: Nes Nepa In Ibdmentioning
confidence: 99%
“…IFNγ activates PI3K/Akt signaling in the mucosa of colitic mice and reduces proliferation [2] , [3] , [14] , [16] , therefore we analyzed mTORC1 status in SW480 and RKO cells treated with IFNγ for 3 h. As shown in Figure 2 A increased phosphorylation of STAT1 phosphorylation at Y701 was observed after IFNγ stimulation demonstrating the functionality of our assay. Furthermore, phosphorylation of Akt at ser473, β-catenin at ser552, mTOR at ser2448 and P70S6K at Thr389 was induced after cytokine treatment.…”
Section: Resultsmentioning
confidence: 71%
“…Rapamycin used as previously reported by us [14] Doxorubicin was obtained from Pfizer and used at 3.45 μM. AZD8055 and XAV939 were used as previously reported by us [16] , [17] . Dextran sulfate sodium YD318041799 (Carbosynth, San Diego, CA) was dissolved at 3% in drinking water.…”
Section: Methodsmentioning
confidence: 99%